(3ebGdI aj COhjI GdJQjGbs - (3SdjeGf Hf MSGf GdCfOdSj CHh OGhO, GdeYQha HGHf oLrdoLd,J (B377 (3g` s
(3ChdgG (B:s
(3bGd SdjeGf Ef GdJQjGb GdaGQhb OhGA Ldjd GdNWQ YXje GdbOQ deG jYQV dge ef VQQ GNJdGa GdCghjI GdhHGFjI s
(3BNQgG (B:s
(3hjfaY ef TQH GdejGg GdeNdaI EPG CNP efg fUa eKbGd HeGA fbjY MH GdeTeT ced GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3Jdjg aGFOI dLGdjfhSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B123 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B258s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs